Laparoscopic-assisted Vecchietti Procedure for Creation of Neovagina in Mayer-Rokitansky-Küster-Hauser Syndrome: Analysis of Two Cases - Boyraz, Gökhan; Selçuk, İlker and Yazıcıoğlu, Aslıhan and Esinler, İbrahim (Gynecology Obstetrics & Reproductive Medicine, 2012)
The aim of this study was to review the application of Vecchietti’s principles to laparoscopy for the creation af neovagina in patients diagnosed with Rokitansky syndrome, the functional and psychological outcomes. A functioning neovagina was performed in both of the subjects. The subjects which are sexually active noted satisfactory intercourse with significant improvements in self-confidence, self-esteem and general well-being in first 6 months follow-up.